Risk factors of pre-eclampsia in Dompu District, West Nusa Tenggara Province - Maria Ulfah; Ni Luh Putu Suariyani; Dyah Pradnyaparamita Duarsa (Public Health and Preventive Medicine Archive, 2017)
Background and purpose: Pre-eclampsia is a major contributing factor of maternal mortality. Dompu District has a high rate of maternal mortality relative to the rest of districts in West Nusa Tenggara Province. Pre-eclampsia is the major cause of maternal mortality in Dompu District. This study aims to examine risk factors of pre-eclampsia among pregnant women. Methods: A case control study was conducted in five public health centres in Dompu District. A total of 104 women who gave birth and have diagnosed with pre-eclampsia during the pregnancy were recruited as cases. A total of 104 women who gave girth and did not have pre-eclampsia were selected as controls. All cases and controls were selected using a systematic random sampling technique from the 2016 pregnant women cohort at five public health centres. Data were collected through interview and extraction from the maternal and child health book. Data were analysed using bivariate and multivariate techniques. Results: Our multivariate analysis found that pre-eclampsia was associated with parity of 1 or >3 (AOR=3.64; 95%CI: 1.85-7.17), body mass index of >27.0 kg/m2 (AOR=3.01; 95%CI: 1.39-6.48), history of chronic diseases (AOR=16.43; 95%CI: 3.32-81.22) and smoke exposure (AOR=3.71; 95%CI: 1.95-7.05). Conclusions: Parity of 1 and >3, BMI of >27.0 kg/m2, history of chronic illnesses and smoke exposure are risk factors for pre-eclampsia in Dompu District, West Nusa Tenggara.